New host and geographical records of Rhytidhysteron in northern Thailand, and species synonymization - Senwanna, Chanokned; Suwannarach, Nakarin; Phookamsak, Rungtiwa; Kumla, Jaturong; Hongsanan, Sinang (Phytotaxa, 2023)
During a survey of micro-fungi in Chiang Mai Province, Thailand, fruiting bodies of Rhytidhysteron growing on dead twigs of several host plants were collected. Phylogenetic analyses of a combined LSU, ITS, SSU, and TEF1 sequence data along with morphological characteristics, were used to identify the new collections as R. bruguierae, R. neorufulum and R. subrufulum which were collected from Murraya paniculata, Rosa × damascena, and Prunus sp., respectively. These Rhytidhysteron species are reported herein from these hosts for the first time. Interestingly, R. subrufulum is the first geographical record of this species from Thailand, which extends knowledge of the geographic range of this species. In addition, we synonymize R. erioi under R. bruguierae and R. mengziense under R. ligustrum based on phylogenetic analyses and morphology.